Assessing the impact of a 6-year health sciences enrichment program for underrepresented minority youth on healthcare workforce diversity, career path, and public health - Oscar B. Kohut; Zhiru Wang; Ronald R. Sanchez; Ronald R. Sanchez; John C. Rausch; Andy Nieto; Mara M. Minguez; Mara M. Minguez (Frontiers Media S.A., 2023)
BackgroundImproving the quality of care for a diverse population requires a diverse healthcare workforce which necessitates high educational attainment among underrepresented communities. Programs aimed to address healthcare workforce diversity gaps also serve as a public health intervention by offering avenues to improve the health of local communities by providing students with the knowledge and skills to promote healthy behaviors, foster scientific literacy, and inspire future public health professionals - who in turn serve their local communities to advance health outcomes. We interviewed alumni of the New York Presbyterian Hospital Lang Youth Medical Program (LYMP), a high school health sciences mentoring and enrichment program for underrepresented minority youth in Upper Manhattan, from graduating classes between 2012 and 2021 to explore their perspectives on what aspects of the program had the most impact on their academic and career paths.MethodThis is a qualitative study using in-depth, semi-structured individual interviews. All interviews were analyzed using the constant comparative method for developing grounded theory, following a convenience sampling method.Results106 codes were organized into 24 themes, which were further arranged into 4 topic areas: demonstrated program success, intangible program drivers, improvement opportunities, and barriers to program participation. Topic areas captured participants' perspectives on how the program is designed to foster an environment of personal, academic, and professional development; ways aspects of the program organically worked together to provide unanticipated positive facilitators; opportunities for program improvements, and external factors that influenced decision-making.ConclusionThrough this study, we found that the LYMP had a positive influence in helping participants set and achieve personal, academic, and professional goals. Alumni reported activities and experiences offered by the program that foster key youth development constructs linked to healthier and more resilient communities. Importantly, the vast majority of participants described how the synergism between program features, staff support, family involvement, and professional development and networking created an environment of achievement that went beyond the scope of the program design. Findings from this study offer a blueprint for other organizations to craft a similarly successful enrichment program that improves health outcomes, reduces health disparities, and promotes overall population health.